Lateral meniscus transplant and oteochondral alograft tansplant in an oympic ski racer - Volz, J. D.; DePhillipo, N. N.; Martin, B. M.; LaPrade, R. F. (Journal of Athletic Training, 2019)
Background: Due to the critical function of the menisci, meniscal tears should be repaired whenever possible due to the detrimental consequences of post-traumatic osteoarthritis and dysfunction associated with meniscectomy. This level 3 CASE study describes an Olympic ski racer who presented with recurrent knee swelling, pain, and inability to ski 1-year status-post partial lateral meniscectomy and subsequent early-onset of osteoarthritis. The patient underwent a lateral meniscus allograft transplant and concomitant osteochondral allograft transplant(OATS) which allowed return to full activities and competition in Olympic level ski racing. Patient: 21 year-old male, Olympic level ski racer presented one year status-post left knee ACL reconstruction with a hamstring autograft and partial lateral meniscectomy. After returning to skiing he reported lateral knee pain after a suspected valgus mechanism. His knee ROM was full and strength was equal bilaterally. His Lachman's was a 1+ with a solid end point, otherwise he was ligamentously stable. MRI showed a medial meniscal tear, lateral meniscal tearing with a flap formation and lateral positioning, and a full thickness chondral defect of the lateral femoral condyle. Intervention or Treatment: A diagnostic arthroscopy was performed which demonstrated lateral meniscus deficiency corresponding with a previous subtotal partial meniscectomy and a full thickness defect of the posterior aspect of the lateral femoral condyle. There was also a complex medial meniscus tear that was repaired. The patient underwent the next staged surgery 5 months later which consisted of a lateral meniscus allograft transplant and an OATS to the lateral femoral condyle. Postoperative therapy began immediately after surgery and focused on knee ROM, edema control, and quadriceps activation exercises. He was nonweight bearing for a total of 8 weeks and slowly weaned off of crutches until week 12 postoperatively. The patient avoided all impact activities for a total of 7 monthsand began his return to skiing protocol at 1-year postoperatively. He was able to pass a functional sports test at 14 months postoperatively and returned to full competition. Outcomes or Other Comparisons: The patient was able to return to high level downhill skiing competition. He successfully returned to Giant Slalom and Super G and finished as a top competitor in the combined event at the United States National Championships. He represented the US Olympic Team at the 2018 Winter Games finishing in the top 30 in three different events. Conclusions: A concomitant OATS and lateral meniscal allograft transplant surgery provides a viable surgical option for athletes to return to previous level of activity. The meniscus should be repaired at all costs with primary tears because a meniscectomy has been associated with early-onset of osteoarthritis and failure to return to preinjury levels in elite athletes. Clinical Bottom Line: The return to high impact activity after an OATS or meniscal transplant is contraindicated in much of the current literature, especially in sports involving impact in knee flexion such as downhill skiing. However, this case shows that proper surgical intervention, with careful recovery / rehab and return to sport, patients are certainly capable of returning to high level competition in high impact sports after major surgical intervention such as an OATS and total meniscus transplant.